Respostas
respondido por:
1
2x + 3y = 10 (-2)
-4x - 6y = -20
Agora some à outra equação:
-4x -6y +4x -y = -20 -1
-7y = -21 :(-7)
y = 3
Substituindo na primeira equação:
2x +3.3 = 10
2x = 10 -9
2x = 1
x = 1/2
----------------------------------------------------------------------------------------------------------------
3x-4y=1 .4
x+3y=9 .4
12x-12=4 elimina o y pois as variáveis são iguais
4x+12y=36
16x=40
x=2.5
-4x - 6y = -20
Agora some à outra equação:
-4x -6y +4x -y = -20 -1
-7y = -21 :(-7)
y = 3
Substituindo na primeira equação:
2x +3.3 = 10
2x = 10 -9
2x = 1
x = 1/2
----------------------------------------------------------------------------------------------------------------
3x-4y=1 .4
x+3y=9 .4
12x-12=4 elimina o y pois as variáveis são iguais
4x+12y=36
16x=40
x=2.5
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás